Survival Benefit of Neoadjuvant Treatment in Clinical T3N0M0 Esophageal Cancer - Mantziari, Styliani (2017)
Background: Based on current guidelines, clinical T3N0M0 esophageal tumors may or may not receive neoadjuvant treatment, according to their perception as locally advanced (cT3) or early-stage tumors (stage II). The study aim was to assess the impact of neoadjuvant treatment upon survival for cT3N0M0 esophageal cancer patients, with subgroup analyses by histological type (squamous cell carcinoma vs adenocarcinoma) and type of neoadjuvant treatment (chemotherapy vs radiochemotherapy). Methods: Data from patients operated on for esophageal cancer in 30 European centers were collected. Among the 382 of 2944 patients with clinical T3N0M0 stage at initial diagnosis (13.0%), we compared those treated with primary surgery (S, n = 193) versus with neoadjuvant treatment plus surgery (NS, n = 189). Results: The S and NS groups were similar regarding their demographic and surgical characteristics. In-hospital postoperative morbidity and mortality rates were comparable between groups. Patients were found to be pN+ in 64.2% versus 42.9% in the S and NS groups respectively (P < 0.001), pN2/N3 in 35.2% versus 21.2% (P < 0.001), stage 0 in 0% versus 16.4% (P < 0.001), and R0 in 81.3% versus 89.4% of cases (P = 0.026). Median overall and disease-free survivals were significantly better in the NS group, 38.4 versus 27.9 months (P = 0.007) and 31.6 versus 27.5 months (P = 0.040), respectively, and this difference remained for both histological types. Radiotherapy did not offer a benefit compared with chemotherapy alone (P = 0.687). In multivariable analysis, neoadjuvant treatment was an independent favorable prognostic factor (HR 0.76, 95% CI 0.58–0.99, P = 0.044). Conclusion: Neoadjuvant treatment offers a significant survival benefit for clinical T3N0M0 esophageal cancer.